Measure of complete dependence of random vectors - Therdsak Boonmee (2018)
© 2016 Elsevier Inc. In this work, we define a family of measures of complete dependence of absolutely continuous random vectors extended those of random variables. We show that these measures satisfy a suitable set of properties to be called measures of complete dependence. Computational examples are also given.